Effects of strain rate and confining pressure on the compressive behavior of Kuru granite. (May 2016) - Hokka, M.; Black, J.; Tkalich, D.; Fourmeau, M.; Kane, A.; Hoang, N.-H.; Li, C.C.; Chen, W.W.; Kuokkala, V.-T.
Highlights: Dynamic compression testing at confining pressures up to 225 MPa. Effects of confining pressure and strain rate on rock strength are discussed. Strain rate sensitivity is influenced by the confinement only at low pressures. Abstract: Understanding the influence of hydrostatic pressure and loading rate on the strength and fracture behavior of rocks is very important for the development of deep drilling technology. This paper presents a systematic study on the mechanical properties and behavior of Kuru Gray granite at confining pressures up to 225 MPa and at strain rates of 10 −6 s −1 and 600 s −1 . The low strain rate compression tests were carried out with a servo-controlled hydraulic testing machine with a radial confining chamber, and the dynamic tests with a special split Hopkinson pressure bar device with axial and radial confining pressure chambers. The results show that the rock strength increases significantly with strain rate and confining pressure. At confinements below 20 MPa, the strength of the material increases faster at the higher strain rate, but at confinements higher than this, the effect of confining pressure is stronger at the lower strain rate. The strain rate sensitivity increases when even a small confining pressure is applied. However, the rate sensitivity remains rather constant when the confining pressure is increased above 10 MPa. The parameters of the Hoek–Brown model and an alternative power-law model were calibrated for low and high rate data. Also, the fracture behavior of the rock was found to be strongly dependent on strain rate and confining pressure. At the low strain rate, the samples fail by axial splitting in the unconfined tests, whereas the dynamic unconfined tests result in a complete pulverization of the samples. At high confining pressures the fracture behavior is shear fracture for both studied strain rates.